Greek Language Education in Egypt: Legitimate Practices of An Ethnocentric Model - Ieronimakis Giannis; Efstathopoulou Aggeliki (Comparative Education Society of Iran ( CESIR), 2018)
The educational content of the Greek language education in Egypt is drawn from the metropolitan centre (Greece) with the aim of developing a national consciousness based on a single ethno-cultural identity (see Greek). Such a choice is debatable as to its feasibility and results in the sense that it contrasts with the conditions of Greek children socialization in the host country (Egypt), which are bilingual, coming from two different cultures, while their education is ethnocentric or oriented around Greece. In our research we examine the reasons that led to an education cut off from the sociocultural reality of the Greeks of the Diaspora, as well as its consequences, given that the Greek community has lost its past dynamics and it is on a declining path. The role of the Greek community has proven to be decisive in educational matters and has largely determined the educational policy of Greece, and partly of Egypt, and, on the other hand, it shaped the attitudes and behaviours of alien residents on this issue. Our analysis reveal the need for an intercultural specification of the ethnic identity in migratory environments in order for this identity to reflect the experiences and living conditions of its bodies.